The study of etiological and demographic characteristics of neonatal mortality and morbidity - a consecutive case series study from Pakistan - Manzar Nabeel; Manzar Bushra; Yaqoob Anum; Ahmed Muneer; Kumar Jai (BMC, 2012)
Abstract Background To determine the etiology, management, bacteriological spectrum and outcome of neonatal patients admitted in Civil Hospital Karachi (CHK) and to examine the factors associated with it. Methods This hospital based descriptive study of 1463 patients from both sexes who were admitted to Paediatric department, CHK from 1st January 2008 till 31st December 2010 with an established cause according to modified Wigglesworth classification and fulfilling other inclusion criteria were included in the study. Data regarding their demographic profile and potential risk factors was collected on a well structured proforma. Cases were followed until discharge or expiry. Data was analyzed using descriptive statistics. Results The male to female ratio in our study was 1.12:1. Seven hundred and thirty-four patients were delivered at home (50.2%) and 1010 were less than 7 days old (69%). Out of the total cohort of expired subjects, 89 participants (74.8%) were < 7 days of life. Mortality was more in neonates born at home in rural areas to illiterate mother; 74 patients (62.2%). Most of the deaths; 57 were in neonates suffering from specific infections (47.9%) followed by 38 deaths in immaturity group (31.9%) and 19 related to asphyxial conditions (15.9%). The most common isolates were Staphylococcus aureus (28.7%) followed by Klebsiella (24.8%) and Pseudomonas aeruginosa (16.6 ). One hundred and nineteen (8.13%) of the neonates died in our study group. Conclusions These results suggest that neonates with illiterate mothers with high parity and below average socioeconomic level were more susceptible to mortality in the early neonatal period. Most of the cases of mortality were due to specific infections.